Child marriage and female circumcision (FGM/C): Evidence from Ethiopia - Pankhurst, A (Young Lives, 2014)
Child marriage and female circumcision are linked practices that are prevalent in Sub-Saharan Africa and common traditions in Ethiopia. Commitment to end them has been expressed by the African Union and Ethiopia has taken a strong stand through legislation, campaigns and concerted action by government, international organisations and civil society. There is recent evidence of significant decrease of both practices, enabling us to draw lessons from Ethiopia as a success case.